2000
DOI: 10.1007/s004970050200
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis homologue of the Drosophila meiotic gene Pelota

Abstract: We have identified a plant homologue of the Drosophila meiotic gene Pelota in Arabidopsis thaliana (AtPelota1). This gene maps to chromosome 4 of Arabidopsis and is one of two Pelota homologues present in this plant. When the expression pattern of AtPelota1 was examined it was found to be expressed at similar levels in all plant tissues tested (whole plant, bud, stem, leaf and root). This expression pattern corresponds to that seen for some other Arabidopsis meiotic genes and their homologues. A search of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…One of these six genes that was very significantly down-regulated at both time points was a Pelota gene (Additional file 3 : Table S7), which was originally identified in Drosophila melanogaster and is known to function in meiosis [ 62 ]. In mouse, it has been reported that disruption of the Pelota gene causes early embryonic lethality and defects in cell cycle progression [ 63 ], and in plants, a single homologue has been identified in Arabidopsis [ 64 ]. Due to its known role in meiosis, it is highly possible that reduction of Pelota expression in grape could be related to GA 3 -induced seedlessness (Figure 2 J).…”
Section: Discussionmentioning
confidence: 99%
“…One of these six genes that was very significantly down-regulated at both time points was a Pelota gene (Additional file 3 : Table S7), which was originally identified in Drosophila melanogaster and is known to function in meiosis [ 62 ]. In mouse, it has been reported that disruption of the Pelota gene causes early embryonic lethality and defects in cell cycle progression [ 63 ], and in plants, a single homologue has been identified in Arabidopsis [ 64 ]. Due to its known role in meiosis, it is highly possible that reduction of Pelota expression in grape could be related to GA 3 -induced seedlessness (Figure 2 J).…”
Section: Discussionmentioning
confidence: 99%
“…No hybridization signals were detected even when 50 µg of total RNA was loaded (data not shown), suggesting that OsDMC1 is expressed at a low level. This difficulty has been encounted when analyzing expression of plant meiotic genes AtDMC1 (Klimyuk and Jones 1997), SYN1 (Bai et al 1999) and AtPelota (Caryl et al 2000) with northern hybridization. We therefore used RT-PCR to analyze expression of this gene.…”
Section: Expression Of Osdmc1mentioning
confidence: 99%
“…Pelota (PELO) is an evolutionarily conserved protein and has been identified in a number of species, including Drosophila (Eberhart and Wasserman, 1995), archaebacteria (Ragan et al, 1996), yeast (Davis and Engebrecht, 1998), Arabidopsis thaliana (Caryl et al, 2000), human (Shamsadin et al, 2000), mouse (Shamsadin et al, 2002) and tomato (Lapidot et al, 2015). The PELO proteins contain 347-395 amino acid residues and RNA-binding domains similar to that found in the family members of the eukaryotic release factor 1 (eRF1) family members, which play roles in termination of protein synthesis (Davis and Engebrecht, 1998).…”
Section: Introductionmentioning
confidence: 99%